Gebruik van twee tale in die Daniëlboek - Nel, Marius (Verbum et ecclesia, 2004)
The Book of Daniel is characterized by a change of language, from Hebrew to Aramaic to Hebrew (in Dan 2:4b to Aramaic and in Dan 8:1 to Hebrew). What caused the change from the ‘sacred’ to a ‘heathen’ language and back? Does the change of language implicate something about the date of origin of the tales (Dan 1-6) and visions (Dan 7-12)? The rabbinical answer to the question and the results of modern research into the book are being investigated. The words "in Aramaic" (in Dan 2:4a) was probably a mistake made by a later scribe when he incorporated a note from the margin into the Biblical text that was used to warn the reader that the language changes at this point. The result is that the text now reads as if the wise men answer the king, who speaks Hebrew, in Aramaic. This leaves the necessary room to speculate that the use of the two languages may have something to do with the process in which the tradition was handed down to the second century writer or redactor of the book.